Influence of antipsychotics on metabolic syndrome risk in patients with schizophrenia - Koricanac, Aleksandra; Tomic Lucic, Aleksandra; Veselinovic, Mirjana; Bazic Sretenovic, Danijela; Bucic, Gorica; Azanjac, Anja; Radmanovic, Olivera; Matovic, Mirjana; Stanojevic, Marijana; Jurisic Skevin, Aleksandra; Simovic Markovic, Bojana; Pantic, Jelena; et al. (Frontiers in Psychiatry, 2022)
Objective Many studies so far have shown that antipsychotic therapy may have an effect on the development of metabolic syndrome in patients diagnosed with schizophrenia. Our goal was to determine whether our respondents are at risk for developing metabolic syndrome and who is more predisposed to it. Methods In a stable phase, 60 patients diagnosed with schizophrenia were equally divided into three groups according to the drug (risperidone, clozapine, and aripiprazole monotherapy). Control group had 20 healthy examinees. Patients were evaluated first using The Positive and Negative Syndrome Scale (PANSS). Prolactin, lipid status, glycemia, insulin, cytokine values (IL-33, TGF-β, and TNF-α) and C-reactive protein (CRP) were measured. Also, Body mass index (BMI), Homeostatic Model Assesment for Insulin Resistance (HOMA index), waist and hip circumference (WHR) and blood pressure (TA) measurement were performed in the study. Results Patients treated with risperidone compared to healthy control subjects and aripiprazol group of patients had statistically significant difference in prolactin levels. In clozapine group compared to healthy control group values of HDL cholesterol and glucose level were statistically significant different. In aripiprazole group compared to healthy control group value of BMI was statistically significant different. Statistically significant correlations were found in TNF-α with glucose and HOMA index in risperidone treated patients and with BMI in clozapine group of patients; IL-33 with glucose in risperidone and with BMI in clozapine group of patients and TGF-β with glucose in risperidone group, with insulin and HOMA index in clozapine group and statistically significant negative correlation with LDL cholesterol in aripiprazole group of patients. Conclusion Patients on risperidone and clozapine therapy may be at greater risk of developing metabolic syndrome than patients treated with aripiprazole. Statistically significant difference in concentration of TNF-α and TGF-β was in the group of patients treated with risperidone compared to healthy control group.